Modelling and Simulation of Transporter Behaviour in Intralogistics Systems - Berdenius Norström, Carl; Wallenfeldt, Victoria (My University, 2026)
Intralogistics systems are essential for enabling efficient material flow in modern manufacturing, yet current discrete-event simulation (DES) approaches often rely on fragmented data and simplified transporter representations, thereby limiting their effectiveness as decision-support tools. This thesis investigates how transporter behavior can be systematically modeled in DES to enable consistent and comparable evaluation of intralogistics solutions. The study is conducted as a qualitative case study at Volvo Car, combining a literature review, semi-structured interviews, and simulation modeling in Tecnomatix Plant Simulation. The results show that standardized, externalized input data support the development of generic, reusable simulation models, thereby reducing manual effort and improving comparability. Furthermore, transporter behavior can be effectively represented using a task-based control logic approach, enabling different transporter types to be implemented within the same framework. The findings indicate that combining standardized data structures with generic model design and behavior logic can enhance reusability and decision support in intralogistics simulation. This thesis provides a foundation for future data-driven and automated DES applications for intralogistics
Keywords: Discrete Event Simulation; Intralogistics; Data Management; Automated Model Generation; Generic Simulation Model; Automotive Industry